Biomarkers and Detection Platforms for Human Health and Performance Monitoring: A Review. Issue 7 (12th January 2022) - Sim, Daniel; Brothers, Michael C.; Slocik, Joseph M.; Islam, Ahmad E.; Maruyama, Benji; Grigsby, Claude C.; Naik, Rajesh R.; Kim, Steve S.
Abstract: Human health and performance monitoring (HHPM) is imperative to provide information necessary for protecting, sustaining, evaluating, and improving personnel in various occupational sectors, such as industry, academy, sports, recreation, and military. While various commercially wearable sensors are on the market with their capability of "quantitative assessments" on human health, physical, and psychological states, their sensing is mostly based on physical traits, and thus lacks precision in HHPM. Minimally or noninvasive biomarkers detectable from the human body, such as body fluid (e.g., sweat, tear, urine, and interstitial fluid), exhaled breath, and skin surface, can provide abundant additional information to the HHPM. Detecting these biomarkers with novel or existing sensor technologies is emerging as critical human monitoring research. This review provides a broad perspective on the state of the art biosensor technologies for HHPM, including the list of biomarkers and their physiochemical/physical characteristics, fundamental sensing principles, and high‐performance sensing transducers. Further, this paper expands to the additional scope on the key technical challenges in applying the current HHPM system to the real field. Abstract : Detecting biomarkers with novel or existing sensor technologies is emerging as critical human monitoring research. This review provides a broad perspective on the state‐of‐art biosensor technologies for human health and performance monitoring, including the list of biomarkers and their physiochemical/physical characteristics, fundamental sensing principles, high‐performance transducers, and the key technical challenges in applying the current system to the real field.